Analisis Tingkat Pencemaran Air Sungai Yeh Sungi di Kabupaten Tabanan Dengan Menggunakan Indikator Biologis NVC Ikan dan Keragaman Jenis Makrozoobenthos - I Gusti Made Arya Sedana; Ni Made Darmadi; I Wayan Arya (GEMA AGRO, 2018)
Water is a major component of life processes on earth, good quantity and quality of water is highly coveted by humans. River as one type of waters and become a living medium for aquatic organisms, to measure the level of water pollution one of them by using bioindicator method. Bioindicators are organisms that have biological responses that can indicate the entry of certain pollutants in the environment. The purpose of this research is to know river pollution based on Nutrition Value Coeficient (NVC) fish and Makrozoobenthos that live in it. The value of NVC (Nutrition Value Coefficient) of fish varies on each station in the downstream and upstream segments of the Yeh Sungi river, this illustrates that at each station and on different river segments shows different levels of pollution. Waters with clean categories up to the contaminated waters will be found larvae insect , insects and snails. So on headwaters with macrozoobenthos conditions like this describe the condition of clean waters up to be contaminated, so if associated with the value of NVC fish then the headwaters of Yeh Sungi including the contaminated waters category.